Medication adherence in pediatric asthma: A systematic review of the literature. Issue 5 (20th February 2018) - Gray, Wendy N.; Netz, Mallory; McConville, Andrew; Fedele, David; Wagoner, Scott T.; Schaefer, Megan R.
Abstract: Objective: To provide a systematic review of correlates of adherence to inhaled corticosteroids (ICS) in pediatric asthma across the individual, family, community, and healthcare system domains. Methods: Articles assessing medication adherence in pediatric asthma published from 1997 to 2016 were identified using PsychINFO, Medline, and CINAHL. Search terms included asthma, compliance, self‐management, adherence, child, and youth. Search results were limited to articles: 1) published in the US; 2) using a pediatric population (0‐25 years old); and 3) presenting original data related to ICS adherence. Correlates of adherence were categorized according to the domains of the Pediatric Self‐Management Model. Each article was evaluated for study quality. Results: Seventy‐nine articles were included in the review. Family‐level correlates were most commonly reported ( N = 51) and included socioeconomic status, race/ethnicity, health behaviors, and asthma knowledge. Individual‐level correlates were second‐most common ( N = 37), with age being the most frequently identified negative correlate of adherence. Health care system correlates ( N = 24) included enhanced asthma care and patient‐provider communication. Few studies ( N = 10) examined community correlates of adherence. Overall study quality was moderate, with few quantitative articles (26.38%) and qualitative articles (21.4%) referencing a theoretical basis for their studies. Conclusions: All Pediatric Self‐Management Model domains were correlated with youth adherence, which suggests medication adherence is influenced across multiple systems; however, most studies assessed adherence correlates within a single domain. Future research is needed that cuts across multiple domains to advance understanding of determinants of adherence.